Design, Synthesis, and In Vitro Antioxidant Activity of 1,3,5-Trisubstituted-2-pyrazolines Derivatives - P. C. Jagadish; Neeraj Soni; Amita Verma (Journal of Chemistry)
Mannich base of pyrazolines 3(a–e) under both conventional and microwave irradiation was synthesized. All the synthesised compounds were purified by recrystallisation, characterized on the basis of UV, IR, and NMR spectroscopy, and further supported by mass spectroscopy. The result obtained confirms superiority of microwave irradiation method over classical heating one. The molecular properties and Lipinski rule of five for compounds 3(a–e) were determined by Molinspiration. The synthesized compounds were subsequently evaluated for the antioxidant activity. All the compounds were found in compliance with Lipinski “Rule of Five”, and compound 3e having p-hydroxyl substitution showed best antioxidant activity as compared to ascorbic acid and rutin.